The Effect of Capital Structure on Firm Value in Banking Companies Listed on the Indonesia Stock Exchange - Sonjaya, Yaya; Muslim, M. (Manunggal Halim Jaya, 2023)
This study is to determine the effect of capital structure on firm value in banking companies on the Indonesia Stock Exchange. The data used is quantitative data. The population in this study were 8 banking companies listed on the Indonesia Stock Exchange, while the sample used in this study used the Purposive Sampling formula of 40. Data collection was carried out through documentation. The data analysis method used is the classic assumption test, regression analysis, and hypothesis testing using SPSS 23 for Windows software. Based on the results of research that examines the effect of the Debt-to-Equity Ratio on Price Book Value, the t value = 4.801 is greater than the t table = 2.02439, with a significance level of 0.060 greater when compared to the α = 5% level, then H1 is accepted. The constant value of 3.826 means that, if the DER variable does not change, then PBV has a value of 3.826. Meanwhile, the DER variable coefficient value of -0.262, means that if DER increases by one percent, PBV decreases by 0.262. These results indicate that statistically DER has a negative and insignificant effect on PBV in Banking Companies listed on the Indonesia Stock Exchange. Thus, the hypothesis stating that DER has a negative and insignificant effect on PBV in Banking Companies listed on the Indonesia Stock Exchange is proven.